An assessment of customers' satisfaction for emerging technologies in passenger cars using Kano model. Issue 1 (14th December 2020) - Kohli, Anu; Singh, Ram
Abstract : Purpose: Automobile industry has been the backbone of manufacturing sector in any country. During the past decade, passenger car industry has emerged as the one of the growing sectors in the Indian economy. Technological features in the passenger cars industry has been evolving in the global market, and customers have been the most important stakeholders to judge the requirement of these features. Therefore, the purpose of this paper is to analyze the customers' need for these emerging technologies using Kano model of customer satisfaction. Design/methodology/approach: This paper has used the Kano model to assess the customer satisfaction for Indian passenger car companies. Overall, 250 customers of passenger cars from Northern India have been surveyed using well-structured questionnaire designed as per the Kano model. On the basis of responses, this study has categorized the technological attributes of passenger cars as attractive, must be, one-dimensional and indifferent. Findings: "Auto Gear Shift" system has emerged as a must be attribute. "Premium surround system" has been categorized under one-dimensional attribute. "Communication between vehicles, " "integration with smart phone, " "connecting applications, " "dual-stage airbags, " "in-dash navigation system, " "rearview camera, " "heated and cooled seats, " "built-in fourth generation long term evolution, " "Wi-Fi system" and "automated window cleaning system" have emerged as attractive features. The customers have been indifferent about "gesture control, " "reality display on car wind screen" and "run-on-flat tyre." In contradiction to the popular belief, this study has found that customers have shown Indifferent attitude toward "hydrogen fuel-operated cars" and "battery cars." Research limitations/implications: This present study gives insight about the acceptability of various emerging technological features in Indian car market. This study has fulfilled the existing dearth in assessing the customers' insight about the implementation of these emerging technologies in Indian cars. This paper will be helpful to the manufacturers to inculcate the voice of the customers in designing the new technologies for the passenger cars. Originality/value: Previous studies across the globe have applied Kano model for assessing customers' satisfaction in various industries, but according to the authors' knowledge, hardly any study was conducted in context of technological attributes for Indian passenger car companies.